Endovascular thrombectomy is cost-saving in patients with acute ischemic stroke with large infarct - Schwarting, Julian; Froelich, Matthias F.; Kirschke, Jan S.; Mehrens, Dirk; Bodden, Jannis; Sepp, Dominik; Reis, Jonas; Dimitriadis, Konstantinos; Ricke, Jens; Zimmer, Claus; Boeckh-Behrens, Tobias; Kunz, Wolfgang G. (Frontiers in Neurology, 2024)
Objective: Endovascular thrombectomy (EVT) is the standard of care for acute large vessel occlusion stroke. Recently, the ANGEL-ASPECT and SELECT 2 trials showed improved outcomes in patients with acute Ischemic Stroke presenting with large infarcts. The cost-effectiveness of EVT for this subpopulation of stroke patients has only been calculated using data from the previously published RESCUE-Japan LIMIT trial. It is, therefore, limited in its generalizability to an international population. With this study we primarily simulated patient-level costs to analyze the economic potential of EVT for patients with large ischemic stroke from a public health payer perspective based on the recently published data and secondarily identified determinants of cost-effectiveness. Methods: Costs and outcome of patients treated with EVT or only with the best medical care based on the recent prospective clinical trials ANGEL-ASPECT, SELECT2 and RESCUE-Japan LIMIT. A A Markov model was developed using treamtment outcomes derived from the most recent available literature. Deterministic and probabilistic sensitivity analyses addressed uncertainty. Results: Endovascular treatment resulted in an incremental gain of 1.32 QALYs per procedure with cost savings of 17,318 per patient. Lifetime costs resulted to be most sensitive to the costs of the endovascular procedure. Conclusions: EVT is a cost-saving (i.e., dominant) strategy for patients presenting with large ischemic cores defined by inclusion criteria of the recently published ANGEL-ASPECT, SELECT2, and RESCUE-Japan LIMIT trials in comparison to best medical care in our simulation. Prospective data of individual patients need to be collected to validate these results